Unsur-unsur Pengetahuan Sosial dalam Cerita Rakyat Bali Aga dan Buku Pelajaran Sekolah Dasar Zaman Kolonial Belanda - Ida Ayu Laksmita Sari (Pusat Kajian Bali Universitas Udayana, 2019)
This article analyses the elements of general knowledge in the folklores of Balinese Bali Aga and in the elementary school-text books of the Dutch colonial period. The analyses focuses on how narrative texts which usually consider as fiction and contain unreal information are also expressing general knowledge and social and cultural facts. The object of this study are selected folktales of Bali Aga published in book form in 1987 and expositional text and short stories included the school text books published in the 1910s. Of the two books, 10 texts were chosen for discussion. Data were analysed with rhetoric and content analysis theories that give attention to the content instead of structure of texts. This article concludes that folklore, short story, and other forms of fictional genre are rich in general knowledge on social and cultural life and description on factual matters similar to expositional text genre. Thus, like expositional texts genre, narrative texts have the ability to tell stories and also to convey varieties of general knowledge related to the society that owned the stories. Keywords: Balinese language, narrative text, expositional text, fact and fiction, content analysis